2009
DOI: 10.1186/1471-2180-9-261
|View full text |Cite
|
Sign up to set email alerts
|

The hemolytic and cytolytic activities of Serratia marcescensphospholipase A (PhlA) depend on lysophospholipid production by PhlA

Abstract: BackgroundSerratia marcescens is a gram-negative bacterium and often causes nosocomial infections. There have been few studies of the virulence factors of this bacterium. The only S. marcescens hemolytic and cytotoxic factor reported, thus far, is the hemolysin ShlA.ResultsAn S. marcescens shlAB deletion mutant was constructed and shown to have no contact hemolytic activity. However, the deletion mutant retained hemolytic activity on human blood agar plates, indicating the presence of another S. marcescens hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 42 publications
1
45
0
1
Order By: Relevance
“…In vitro experiments previously demonstrated that purified PhlA could induce cytotoxicity in human bladder and cervical epithelial cells (3), and the Y. enterocolitica PhlA homolog has been proposed to have a role in pathogenesis during murine gastrointestinal infection (14). The partial loss of fitness for bacteria lacking PhlA observed in this work is intriguing, though not definitive.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments previously demonstrated that purified PhlA could induce cytotoxicity in human bladder and cervical epithelial cells (3), and the Y. enterocolitica PhlA homolog has been proposed to have a role in pathogenesis during murine gastrointestinal infection (14). The partial loss of fitness for bacteria lacking PhlA observed in this work is intriguing, though not definitive.…”
Section: Discussionmentioning
confidence: 99%
“…1C and 3A). Indeed, Shimuta et al have indicated that S. marcescens utilizes phospholipase A to exploit hemolytic and cytotoxic effects and potentially to regulate hemolysin ShlA activity (56). Intriguingly, synthesis of phospholipase is positively regulated by FlhDC in S. marcescens (21,37), indicating that the higher hemolytic and cytotoxic activities of S. marcescens ⌬rssBA-shlBA might be due to upregulation of flhDC expression, which further induces phospholipase production.…”
Section: Discussionmentioning
confidence: 99%
“…While the ShlAB hemolysin of S. marcescens is contact dependent, an extracellular hemolysin was described in 1989 and was recently characterized (153,351). This hemolysin, PhlA, has phospholipase A activity (351).…”
Section: Enzymes Produced By Serratia Speciesmentioning
confidence: 99%
“…This hemolysin, PhlA, has phospholipase A activity (351). PhlA does not apparently have direct cytolytic activity; however, it acts upon phospholipid and produces lysophospholipid, which was cytolytic for human, horse, and sheep red blood cells and the HeLa and 5637 cell lines (351).…”
Section: Enzymes Produced By Serratia Speciesmentioning
confidence: 99%